Production of the soybean epoxide hydrolase mutants at Asp101 (D101) site by the PCR Technique - Minh, Nghiem Ngoc; Fukazawa, Chikafusa (Academia Journal of Biology, 2015)
The epoxide hydrolases are widely distributed among many species, including bacteria, fungi, plants and mammals. These enzymes are an interesting group of functionnally related enzymes that catalyse the addition of water molecule to an epoxide (oxirane moiety), producing the corresponding 1-2 diol. Recent studies have been provided valuable information on the molecular structure of these enzymes, as well as insight to the enzymatic mechanisms that  involved. In this report, we demonstrate the production of the soybean epoxide hydrolase mutants at Asp101 site (D101E, D101Q, D101C, D101T, D101H, D101S) by the PCR technique, using the taget mutant primers. Employing the 1st PCR products as primer and the EH- End-Anti 2 primer, the entire cDNA fragment (nearly 1kb) consisted of target mutants encoding epoxide hydrolase from the soybean seeds was obtained by PCR. The cloning and the sequencing of this EH gien were also performanced.